Challenges in developing a quantitative method of measuring breast development using 3D imaging: An example of a novel method for use in induced breast development with exogenous oestrogen. (28th August 2022) - Burt, Elizabeth; Ruff, Clifford; Yasmin, Ephia; Davies, Melanie; Cameron‐Pimblett, Antoinette; Butler, Gary; Conway, Gerard
Abstract: Objective: Optimal breast development is an essential part of exogenous oestrogen treatment in females undergoing pubertal induction. We set out to develop a novel technique using three‐dimensional (3D) imaging to determine change in breast volume that is applicable when no pre‐existing breast contours are present. Design: A prospective observational study. Patients: The imaging methodology was developed using a single male subject to assess reproducibility and validity. The technique was then applied to 29 participants undergoing pubertal induction with exogenous oestradiol who were recruited from Paediatric Gynaecology and Reproductive Endocrinology clinics at University College London Hospital. Measurements: Breast images were taken using a 3D photographic system. Two images, taken at different times, were manually superimposed to produce a differential breast volume. The initial step of method development set out to show that volume change was not secondary to positioning artefact or image manipulation. This was established by using images of a male participant taken on different occasions. The technique was then used to assess reproducibility in participants undergoing pubertal induction treatment. Results: Good intraobserver reproducibility (intraclass correlation (ICC) 0.77) was demonstrated with static image manipulation. Validity of the imaging technique was established as there was no significant difference between the known reference volume produced by computer generated warping and that calculated by manual image manipulation. There was excellent intraobserver reproducibility for breast volume calculation in participants undergoing induced breast development (ICC 0.99). Conclusions: 3D imaging is a promising novel tool to provide quantitative breast volume assessment in individuals undergoing breast induction with exogenous oestradiol treatment.